2015
DOI: 10.1111/bjhp.12172
|View full text |Cite
|
Sign up to set email alerts
|

The threatened self: Considerations of time, place, and uncertainty in advanced illness

Abstract: What is already known on this subject? Loss of self or personal identity occurs in a range of serious conditions. The sick self is incorporated in a process of identity reconstruction. Uncertainty is an inherent aspect of serious and advanced illness. Unmanaged uncertainty results in a range of negative psychological consequences that contribute to the loss of personal identity. Information and communication with health care professionals help patients manage uncertainty. What does this study add? Sufferers ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 57 publications
(53 reference statements)
1
17
0
3
Order By: Relevance
“…The participants also wanted annual checkups on their disease, to confirm or reject any progression. These are good examples of how access to the healthcare services, social support, and confidence with regard to getting help 2 , 5 , 16 improve health in a COPD trajectory. The participants’ assessment of the helpers’ level of insight into the problems associated with COPD emerged as an important phenomenon in the creation of trust in the interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants also wanted annual checkups on their disease, to confirm or reject any progression. These are good examples of how access to the healthcare services, social support, and confidence with regard to getting help 2 , 5 , 16 improve health in a COPD trajectory. The participants’ assessment of the helpers’ level of insight into the problems associated with COPD emerged as an important phenomenon in the creation of trust in the interaction.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Persons living with COPD have experienced that the health-care services are able to accommodate health-enhancing transitions when they experience common understanding and social support and feel confident with regard to getting help. 5 , 16 Difficulties in the communication between patients and health-care personnel and an experience of stigmatization may hinder beneficial processes. 17 19 Identification of transitions and vulnerable phases and knowledge on what may further enhance or hinder good transitions are important in order to understand the conditions for collaborative self-management.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty is not necessarily a negative entity: it is patients’ appraisal and response to uncertainty that mediates its impact. 5 , 7 , 10 For example, some patients will find prognostic uncertainty protective, as it allows them to ‘look on the bright side’, while others find not knowing what will happen distressing.…”
Section: Introductionmentioning
confidence: 99%
“…Both the loss of identity and independence established in this study are similar to those found in other chronic illnesses [ 39 , 40 ]. The unpredictability and uncertainty of diagnosis and treatment of periprosthetic infection draw parallels with patients’ perceptions of multiple sclerosis [ 41 ], HIV [ 42 – 44 ], and cancer [ 45 ]. The disruption to the life course that patients in this study experienced is similar to those experiencing HIV and cancer diagnoses [ 46 48 ].…”
Section: Discussionmentioning
confidence: 99%